Measuring and Modeling Oxygen Transport and Consumption in 3D Hydrogels Containing Chondrocytes and Stem Cells of Different Tissue Origins. - Buckley, Conor; Kelly, Daniel (My University, 2021)
Understanding how the local cellular environment influences cell metabolism, phenotype and matrix synthesis is crucial to engineering functional tissue grafts of a clinically relevant scale. The objective of this study was to investigate how the local oxygen environment within engineered cartilaginous tissues is influenced by factors such as cell source, environmental oxygen tension and the cell seeding density. Furthermore, the subsequent impact of such factors on both the cellular oxygen consumption rate and cartilage matrix synthesis were also examined. Bone marrow derived stem cells (BMSCs), infrapatellar fat pad derived stem cells (FPSCs) and chondrocytes (CCs) were seeded into agarose hydrogels and stimulated with transforming growth factor-β3 (TGF- β3). The local oxygen concentration was measured within the center of the constructs, and numerical modeling was employed to predict oxygen gradients and the average oxygen consumption rate within the engineered tissues. The cellular oxygen consumption rate of hydrogel encapsulated CCs remained relatively unchanged with time in culture. In contrast, stem cells were found to possess a relatively high initial oxygen consumption rate, but adopted a less oxidative, more chondrocyte-like oxygen consumption profile following chondrogenic differentiation, resulting in net increases in engineered tissue oxygenation. Furthermore, a greater reduction in oxygen uptake was observed when the oxygen concentration of the external cell culture environment was reduced. In general, cartilage matrix deposition was found to be maximal in regions of low oxygen, but collagen synthesis was inhibited in very low (less than 2%) oxygen regions. These findings suggest that promoting an oxygen consumption profile similar to that of chondrocytes might be considered a key determinant to the success of stem cell-based cartilage tissue engineering strategies
PUBLISHED
Keywords: tissue grafts; fat pad derived stem cells (FPSCs); chondrocytes (CCs); tissue grafts; fat pad derived stem cells (FPSCs); chondrocytes (CCs)